(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
In an attempt we are assessing a clinical study, knowledge, awareness and preventive measures acknowledgment of Communicable Diseases such as Dengue and Malaria among patients in Tertiary Care Hospital Versus Government Hospital in Khammam, to compare the probability of communicable disease such as Dengue and Malaria in selected Hospital. To compare the prevalence of Dengue and Malaria among Urban and Rural people in selected hospitals. The present study was a multi-cantered prospective observational study conducted in Mamatha General Hospital and Khammam Government Hospital, Khammam, Telangana, India. The total number of cases collected during the study period 6 months was 500. A multi-centered prospective observational study. The major finding of this study is that the probability of Communicable diseases such as Malaria and Dengue among patients. In this study the population is 500, the highest Prevalence is Dengue i.e. 465(93%) than Malaria i.e. 35(7%). In these Female patients are high i.e. 252 compared to Male i.e. 248. According to study evaluation females are more affected. The occurrence of Dengue is observed in the Age group of 41-50 years i.e. 90 patients. The Rural group related patients i.e. 342 are more when compared to urban group related patients i.e. 158. The present multi-centered prospective observational study was conducted in subjects(n=500) from inpatients of Department of General Medicine, Mamatha General Hospital and Khammam Government Hospital, Khammam, Telangana, India, to assess the Probability of Malaria and Dengue, Knowledge assessment among patients about Malaria and Dengue, and also Acknowledging the patients about Dengue and Malaria.